Political and economic impact generated by false positive of military forces in colombia in 2010 (2013)
Colombia comes from a story full of internal conflicts and policies serving only a few , scene multiplier acts in violation of Human Rights and State Crimes that are intertwined with the actions of armed actors such as guerrilla , paramilitary and / or its successors and the security forces, executive without overwhelming response at least to relate to it as their responsibility , as in the case of false positives ; understood as those used in life or death as a course operational successes of the military established as extrajudicial executions, without that fact despite the scandal unleashed in 2008 by the mothers of Soacha and which gave some insight that was not an isolated or civil new in the nation has meant legal or budgetary changes against the armed forces of the state, and even more when in 2010 it was established that these practices did not disappear if not raised before 2009.